Recent Advances in IL-13Rα2-Directed Cancer Immunotherapy - Knudson, Karin M.; Hwang, SuJin; McCann, Mondona S.; Joshi, Bharat H.; Husain, Syed R.; Puri, Raj K. (Frontiers in Immunology, 2022)
Interleukin-13 receptor subunit alpha-2 (IL-13Ra2, CD213A), a high-affinity membrane receptor of the anti-inflammatory Th2 cytokine IL-13, is overexpressed in a variety of solid tumors and is correlated with poor prognosis in glioblastoma, colorectal cancer, adrenocortical carcinoma, pancreatic cancer, and breast cancer. While initially hypothesized as a decoy receptor for IL-13-mediated signaling, recent evidence demonstrates IL-13 can signal through IL-13Ra2 in human cells. In addition, expression of IL-13Ra2 and IL-13Ra2-mediated signaling has been shown to promote tumor proliferation, cell survival, tumor progression, invasion, and metastasis. Given its differential expression in tumor versus normal tissue, IL-13Ra2 is an attractive immunotherapy target, as both a targetable receptor and an immunogenic antigen. Multiple promising strategies, including immunotoxins, cancer vaccines, and chimeric antigen receptor (CAR) T cells, have been developed to target IL-13Ra2. In this mini-review, we discuss recent developments surrounding IL-13Ra2-targeted therapies in pre-clinical and clinical study, including potential strategies to improve IL-13Ra2-directed cancer treatment efficacy.